THE PRINCIPALS’ EFFORTS IN FACILITATING THE FREEDOM TO LEARN BY ENHANCING COMMUNITY PARTICIPATION IN INDONESIA - Maisyaroh Maisyaroh; Juharyanto Juharyanto; Ibrahim Bafadal; Bambang Budi Wiyono; Nova Syafira Ariyanti; Maulana Amirul Adha; Muhammad Imran Qureshi (Jurnal Cakrawala Pendidikan, 2021)
The latest ‘freedom to learn’ policy, issued by the Minister of Education and Culture of the Republic of Indonesia, must be implemented by educational institutions at various levels. The principals played significant roles such as community empowerment to utilize all resources in the schools to support the policy. The research aimed to describe the principals’ efforts in improving community participation in the school and to describe the social involvement in facilitating the freedom to learn at schools. This study employed a qualitative approach with a multi-case research design, and it was conducted in Indonesia, particularly in Tana Tidung Regency in North Kalimantan, Bondowoso Regency in East Java, and Malang City in East Java. The data collection techniques included in-depth interviews and document studies, and to validate the data used a credibility technique. The data validation through the credibility technique was carried out by conducting triangulation, checking members, and improving the persistence and adequacy of reference materials. The cross-case data analysis in this study applied a constant comparative method. The analysis was conducted in all three cases resulted in the provisional findings, continued by data comparison that would later be found by the three cases. The results of this research were the principals’ efforts in enhancing community participation through cooperation with several related parties. The principals were regarded as role models in supporting the ‘freedom to learn’ policy and building cooperation with related partners. The kind of community participation varied based on the uniqueness of each region.